Kodular: A Solution to Create an Instructional Material for Mobile Learning-Based Teaching Writing Skills in the Era Society 5.0 - Cahyo Hasanudin; Subyantoro Subyantoro; Ida Zulaeha; Rahayu Pristiwati (International Conference on Science, Education, and Technology, 2021)
Learning in the era of society 5.0 requires 4C life skills (Creativity, Critical Thinking, Communication, Collaboration) through mastering several literacy skills, such as digital literacy. This study aims to analyze the role of kodular as a website for making mobile learning teaching materials for writing skills courses. This research is an exploratory description research with the research subject is a codedular website user. Research data obtained through observation, questionnaires, and interviews. The results of the observation found that the naming of different courses for writing materials and teaching materials for writing skills courses were still in the printed version. The results of the questionnaire show that the kodular website is more widely used by students than by lecturers. They use a coded website to create learning materials/materials. As many as 80% of respondents agree that the kodular website plays a very important role in the success of learning in the era of society 5.0 and can be used in preparing teaching materials for writing skills courses. The results of the interview show that there are five steps in compiling teaching materials for writing skills courses by paying attention to the components that must be present when using a coded website. The conclusions of this study indicate that the kodular website can be used as a solution in making mobile learning-based teaching materials in writing skills courses to support learning in the era of society 5.0 because the kodular website is based on the Android operating system using block programming.